Determinants of the decline in mortality from acute stroke in England: linked national database study of 795869 adults - Seminog, OO; Scarborough, P; Wright, FL; Rayner, M; Goldacre, MJ (BMJ Publishing Group, 2019)
Objectives: To study trends in stroke mortality rates, event rates, and case fatality, and to explain the extent to which the reduction in stroke mortality rates was influenced by changes in stroke event rates or case fatality.